Convert -12 Fahrenheit to Celsius

What is -12 degrees Fahrenheit in Celsius? Just type in either box, and the number in the other box will be converted automatically.
Fahrenheit
Celsius
-12° Fahrenheit = -24.44° Celsius
(rounded to 4 digits)
How hot is -12 degrees Fahrenheit? How cold? Convert between Fahrenheit and Celsius.
More temperatures starting with -12 degrees in Fahrenheit
Note: results are rounded
-12.00 °F = -24.44 °C -11.75 °F = -24.31 °C -11.50 °F = -24.17 °C -11.25 °F = -24.03 °C
-11.99 °F = -24.44 °C -11.74 °F = -24.30 °C -11.49 °F = -24.16 °C -11.24 °F = -24.02 °C
-11.98 °F = -24.43 °C -11.73 °F = -24.29 °C -11.48 °F = -24.16 °C -11.23 °F = -24.02 °C
-11.97 °F = -24.43 °C -11.72 °F = -24.29 °C -11.47 °F = -24.15 °C -11.22 °F = -24.01 °C
-11.96 °F = -24.42 °C -11.71 °F = -24.28 °C -11.46 °F = -24.14 °C -11.21 °F = -24.01 °C
-11.95 °F = -24.42 °C -11.70 °F = -24.28 °C -11.45 °F = -24.14 °C -11.20 °F = -24.00 °C
-11.94 °F = -24.41 °C -11.69 °F = -24.27 °C -11.44 °F = -24.13 °C -11.19 °F = -23.99 °C
-11.93 °F = -24.41 °C -11.68 °F = -24.27 °C -11.43 °F = -24.13 °C -11.18 °F = -23.99 °C
-11.92 °F = -24.40 °C -11.67 °F = -24.26 °C -11.42 °F = -24.12 °C -11.17 °F = -23.98 °C
-11.91 °F = -24.39 °C -11.66 °F = -24.26 °C -11.41 °F = -24.12 °C -11.16 °F = -23.98 °C
-11.90 °F = -24.39 °C -11.65 °F = -24.25 °C -11.40 °F = -24.11 °C -11.15 °F = -23.97 °C
-11.89 °F = -24.38 °C -11.64 °F = -24.24 °C -11.39 °F = -24.11 °C -11.14 °F = -23.97 °C
-11.88 °F = -24.38 °C -11.63 °F = -24.24 °C -11.38 °F = -24.10 °C -11.13 °F = -23.96 °C
-11.87 °F = -24.37 °C -11.62 °F = -24.23 °C -11.37 °F = -24.09 °C -11.12 °F = -23.96 °C
-11.86 °F = -24.37 °C -11.61 °F = -24.23 °C -11.36 °F = -24.09 °C -11.11 °F = -23.95 °C
-11.85 °F = -24.36 °C -11.60 °F = -24.22 °C -11.35 °F = -24.08 °C -11.10 °F = -23.94 °C
-11.84 °F = -24.36 °C -11.59 °F = -24.22 °C -11.34 °F = -24.08 °C -11.09 °F = -23.94 °C
-11.83 °F = -24.35 °C -11.58 °F = -24.21 °C -11.33 °F = -24.07 °C -11.08 °F = -23.93 °C
-11.82 °F = -24.34 °C -11.57 °F = -24.21 °C -11.32 °F = -24.07 °C -11.07 °F = -23.93 °C
-11.81 °F = -24.34 °C -11.56 °F = -24.20 °C -11.31 °F = -24.06 °C -11.06 °F = -23.92 °C
-11.80 °F = -24.33 °C -11.55 °F = -24.19 °C -11.30 °F = -24.06 °C -11.05 °F = -23.92 °C
-11.79 °F = -24.33 °C -11.54 °F = -24.19 °C -11.29 °F = -24.05 °C -11.04 °F = -23.91 °C
-11.78 °F = -24.32 °C -11.53 °F = -24.18 °C -11.28 °F = -24.04 °C -11.03 °F = -23.91 °C
-11.77 °F = -24.32 °C -11.52 °F = -24.18 °C -11.27 °F = -24.04 °C -11.02 °F = -23.90 °C
-11.76 °F = -24.31 °C -11.51 °F = -24.17 °C -11.26 °F = -24.03 °C -11.01 °F = -23.89 °C